A Comprehensive Review: Interaction of Appearance and Behavior, Artificial Skin, and Humanoid Robot - Nguyen Minh Trieu; Nguyen Truong Thinh (Journal of Robotics)
The development of robotics is undeniable in recent years. Many developing contries face the growth of the elderly population, it is the premise and impetus for the development of research on humanoid robots to serve humans. Many studies on various aspects of robotics are carried out in different parts of the world. Many novel methods were introduced for the design of the robot’s external appearance, internal mechanisms, and gestures. Recent research on humanoid robots is designed to appear to be copies of the anthropometric indicators of real people, which may affect the security of other people’s identities. Besides, these robots cause a feeling of horror in the user if their appearance is in the position of the uncanny valley. Therefore, these designs need to be carefully considered before fabrication. Artificial skin is studied for various purposes such as ensuring collision safety for industrial users and helping robots to perceive basic tactile sensations. This review consists of the recent literature on the interaction of appearance and behavior of robot interaction, artificial skin, and especially humanoid robots, including appearance, such as android and Geminoid robots. This work can provide a reference for humanoid robot research, including uncanny valley hypotheses, artificial skin, and humanoid robots.